Unlocking the sky : Glenn Hammond Curtiss and the race to invent the airplane - Shulman, Seth. (New York : HarperCollins, Publishers, 2002)
Tells the story of Glenn Hammond Curtiss and his quest to construct a reliable and stable airplane, discussing his collaboration with engineers around the world, and the opposition he received from Orville and Wilbur Wright who sued in an attempt to keep Curtiss out of the market.
Part 1. Rewriting aviation history : Intrigue at Hammondsport -- Wrights and wrongs -- America or bust -- Part 2. Reaching for the sky : Captains of the air -- Sky dancing -- Flight of the June Bug -- Sky king -- Part 3. Warped wings : Grounded -- Flight of a hero -- New beginnings -- Epilogue : All but the legacy.
Includes bibliographical references (p. [235]-243) and index.
Keywords: Curtiss, Glenn Hammond, -- 1878-1930.; Airplanes -- History; Air pilots -- United States -- Biography